Effectiveness of beta-blockers depending on the genotype of congenital long-QT syndrome: A meta-analysis - Ahn, Jinhee (PLoS One, 2017)
BACKGROUND: Beta-blockers are first-line therapy in patients with congenital long-QT syndrome (LQTS). OBJECTIVE: This study sought to determine the differences in effectiveness of beta-blockers on risk reduction according to LQTS genotype. METHODS: We searched MEDLINE, EMBASE, and CENTRAL databases to investigate the use of beta-blockers (atenolol, nadolol, propranolol, and metoprolol) in patients with LQTS. Hazard ratio (HR) and relative risk (RR) were extracted or calculated from studies reporting cardiac events (syncope, aborted cardiac arrest (ACA), or sudden cardiac death (SCD)). RESULTS: Among 2,113 articles searched, 10 studies (7 registry-based cohort studies (Cohort) and 3 interrupted time series studies (ITS)) involving 9,727 patients were included. In a meta-analysis using a random-effect model, the use of beta-blocker was associated with significant risk reduction of all cardiac events (HR 0.49, p<0.001 in Cohort; RR 0.39, p<0.001 in ITS) and serious cardiac events (ACA or SCD) (HR 0.47, p<0.001 in Cohort). In both LQT1 and LQT2, the risk was reduced with beta-blocker therapy in Cohort (HR 0.59 in LQT1; HR 0.39 in LQT2) as well as ITS (RR 0.29 in LQT1; RR 0.48 in LQT2). Among the beta-blockers, nadolol showed a significant risk reduction in both LQT1 and LQT2 (HR 0.47 and 0.27, respectively), whereas atenolol and propranolol decreased the risk only in LQT1 (HR 0.36 and 0.46, respectively). Metoprolol showed no significant reduction in either genotype. In LQT3, beta-blocker therapy was not as effective as LQT1 or LQT2; however, it was inconclusive due to data insufficiency. CONCLUSION: This meta-analysis showed that beta-blockers were effective in reducing risk of cardiac events in patients with LQTS. Among them, nadolol was effective in LQT1 and LQT2, whereas other drugs showed different effectiveness depending on LQT genotype.